Pijat Oksitosin sebagai Upaya Meningkatkan Produksi ASI di RS Ken Saras - Samsi Rohmini; Azelia Dewianti; Dewi Nuraini Suci; Ida Sofiyanti; Vistra Veftisia (Universitas Ngudi Waluyo, 2024)
Exclusive breast milk is breast milk that is given to babies from birth for 6 months, without adding or replacing other foods or drinks. The cause of the lack of exclusive breastfeeding is influenced by several factors, one of which is the unsmooth production of breast milk. The purpose of this service is to increase knowledge and understanding of oxytocin massage as an effort to increase breast milk production. The method used was observation with 30 maternal respondents. Maternal service contains the problem of the mother's lack of knowledge about oxytocin massage as an effort to increase breast milk production, with a solution: This activity was carried out for postpartum mothers which we carried out in the diamond room of Ken Saras Hospital. The first stage is to conduct an assessment of the knowledge of postpartum mothers about oxytocin massage. The second stage is to socialize mothers and families to carry out oxytocin massage using leaflet media. The third stage is to evaluate the mother's knowledge about oxytocin massage. The results of the service are expected to be able to be an additional knowledge and insight for mothers. Abstrak ASI eksklusif adalah ASI yang diberikan kepada bayi sejak lahir selama 6 bulan, tanpa menambahkan atau menggantikan makanan atau minuman lain. Penyebab belum tercapainya pemberian ASI ekslusif dipengaruhi oleh beberapa faktor salah satunya adalah tidak lancar produksi ASI. Tujuan dari pengabdian ini untuk meningkatkan pengetahuan dan pemahaman pijat oksitosin sebagai upaya meningkatkan produksi ASI. Metode yang digunakan adalah observasi dengan 30 responden ibu. Pengabdian pada ibu berisi permasalahannya tentang kurangnya pengetahuan ibu mengenai pijat oksitosin sebagai upaya meningkatkan produksi asi, dengan solusi : Kegiatan ini dilakukan pada ibu postpartum yang kami lakukan di ruang intan RS Ken Saras. Tahap pertama adalah melakukan pengkajian terhadap pengetahuan ibu postpartum tentang pijat oksitosin. Tahap kedua melakukan sosialisasi kepada ibu dan keluarga untuk melaksanakan pijat oksitosin dengan menggunakan media leaflet. Tahap ketiga adalah melakukan evaluasi terhadap pengetahuan ibu tentang pijat oksitosin. Hasil dari pengabdian diharapkan mampu menjadi tambahan pengetahuan dan wawasan ibu.